Washington on Washington - Washington, George, 1732-1799 (Book collections on Project MUSE., 2003)
"For most Americans, George Washington is more of a legend than a man - a face on our currency or an austere figure standing in a rowboat crossing the icy Delaware River. He was equally revered in his own time. At the helm of a country born of idealism and revolution, Washington reluctantly played the role of demigod that the new nation required - a role reconciling the rhetoric of democracy with the ritual of monarchy."--Jacket.